Impact of Corporate Governance on the Financial Performance of Financial Institutions in Malaysia - Kumar, Srimeenakshi (Curtin University, 2017)
The objective of the study is to determine the impact of corporate governance (audit committee, board composition and board size) on the financial performance (return on asset and return of equity) of financial institutions, based on agency theory. This study analyses 83 licensed financial institutions in Malaysia, for the period of 2014 and the data was collected from annual reports. The study applied multiple regression model. The findings of the study shows that audit committee and board size has a significant impact on ROA and ROE. Board composition has non-significant impact on ROA and ROE.